A study of the importance of Occupational Safety & Health Act 1994(OSHA) at laboratory at UiTM Shah Alam / Wan Mohd Faiz Abdullah - Abdullah, Wan Mohd Faiz (Faculty of Architecture, Planning and Surveying, 2013)
The safety and health of all employees should be the first priority and value of any business.lt should therefore be the policy of any business to provide a safe and healthful work environment for all of its employees.The business or institution like university should have in place a continuous .safety and health to fulfil and acheve the goal and objective. With this is in mind the safety rules contained in Occupational Safety and Health Act(OSHA) have been formulated to assist and protect us.They were revised to keep up with the latest technological developments,changing conditions and improvements in equipment and procedures as well as the requirements set forth by the OSHA team. Safety pays and it is a good investment for all corcemed.lt eliminates suffering and lost wages.lt also improves production,maintain efficiency,reduces waste and generally provides a sense of well being for all employees and working places. With such a broad definition, no wonder it is nearly impossible to get people who can very commit to a specific safety plan or safety procedure. The government attempts and efforts to define and guide what exactly makes a work area safe, but if everyone doesn't believe the definition or explanation and not take the appropriate action to obey the rules, then the system will break down. Companies or employers that have excellent safety records develop a safety culture where everyone believes that certain safety acts or procedures need to be followed in order to have a safe work area. There are even presentations by motivational speakers, who are really understand about safety, can focus on changing the audience's attitude towards safety. Making people aware of their surroundings and how safe they are is an important factor in getting the buy-in that is needed to have a truly safe work environment. (Fouch, 2011) In fact, it is a very difficult task to implement safety. From year to year, the accidents are continuously happening and the numbers of the accident are still increasing. Even though the number of accidents increase, we still unable to identify specifically what does it mean by safety and find the best way to provide a work environment that are really safe. Further more, when discuss about safety, it can relate with it to the health. Health and safety are very interrelated each other and it is an issue affecting all businesses around the world. One of the efforts to provide the working environment that have both(safety and health) is by implementing an Occupational Safety and Health. It is a legal requirement in many countries includes Malaysia .At Malaysia, it known as Occupational Safety & Health Act 1994(OSHA). OSHA has in recent years become an even more important part of the activities of both the private and public sector. All the sectors acknowledge the relevance of OSHA and they try to implement it as much as they can.OSHA was widely criticized in its early years for confusing, burdensome regulations. A good deal of the early conflict came about because of arbitrary and inconsistent enforcement during OSHA’s early years.